(untitled) (Al-Farooq Journal of Sciences, 2026)
Organic fertilization is essential for increasing agricultural land productivity and reducing environmental pollution caused by the overuse of mineral (chemical) fertilizers. Organic matter indirectly affects the physical, chemical, and biological properties of the soil. It also influences soil acidity, texture, composition, and fertility. Organic matter provides plants with nutrients released from organic compounds and supplies microorganisms with energy and essential materials. Biofertilizers contribute to increased biological activity and root surface area. Furthermore, organic matter acts as a natural soil conditioner, playing a vital and effective role in improving soil properties. Organic fertilizers are characterized by their rapid action, natural origin, and reduced need for chemicals, thus limiting environmental pollution. They are also cost-effective, making them a cost-efficient solution for agriculture. Furthermore, they improve the soil by increasing organic matter, which stimulates biological growth by providing essential nutrients without the need for chemical fertilizers. Bio fertilizers can be used on various crops and are particularly beneficial in organic farming. They can be used primarily in poor soils in arid and semi-arid regions, along with rationalizing irrigation practices. As the world moves towards sustainable agriculture, biofertilizers offer a natural solution to ensure good production and improve soil quality for sustainable farming.